Significant association between renal function and area of amyloid deposition in kidney biopsy specimens in both AA amyloidosis associated with rheumatoid arthritis and AL amyloidosis. (3rd April 2017) - Kuroda, Takeshi; Tanabe, Naohito; Hasegawa, Eriko; Wakamatsu, Ayako; Nozawa, Yukiko; Sato, Hiroe; Nakatsue, Takeshi; Wada, Yoko; Ito, Yumi; Imai, Naofumi; Ueno, Mitsuhiro; Nakano, Masaaki; et al.
Abstract: The kidney is a major target organ for systemic amyloidosis, which results in proteinuria and an elevated serum creatinine level. The clinical manifestations and precursor proteins of amyloid A (AA) and light-chain (AL) amyloidosis are different, and the renal damage due to amyloid deposition also seems to differ. The purpose of this study was to clarify haw the difference in clinical features between AA and AL amyloidosis are explained by the difference in the amount and distribution of amyloid deposition in the renal tissues. A total of 119 patients participated: 58 patients with an established diagnosis of AA amyloidosis (AA group) and 61 with AL amyloidosis (AL group). We retrospectively investigated the correlation between clinical data, pathological manifestations, and the area occupied by amyloid in renal biopsy specimens. In most of the renal specimens the percentage area occupied by amyloid was less than 10%. For statistical analyses, the percentage area of amyloid deposition was transformed to a common logarithmic value (Log10 %amyloid). The results of sex-, age-, and Log10 %amyloid-adjusted analyses showed that systolic blood pressure (SBP) was higher in the AA group. In terms of renal function parameters, serum creatinine, creatinine clearance (Ccr) and estimated glomerular filtration rate (eGFR) indicated significant renal impairment in the AA group, whereas urinary protein indicated significant renal impairment in the AL group. Pathological examinations revealed amyloid was predominantly deposited at glomerular basement membrane (GBM) and easily transferred to the mesangial area in the AA group, and it was predominantly deposited at in the AL group. The degree of amyloid deposition in the glomerular capillary was significantly more severe in AL group. The frequency of amyloid deposits in extraglomerular mesangium was not significantly different between the two groups, but in AA group, the degree amyloid deposition was significantly more severe, and the deposition pattern in the glomerulus was nodular. Nodular deposition in extraglomerular mesangium leads to renal impairment in AA group. There are significant differences between AA and AL amyloidosis with regard to the renal function, especially in terms of Ccr, eGFR and urinary protein, even after Log10%amyloid was adjusted; showing that these inter-group differences in renal function would not be depend on the amount of renal amyloid deposits. These differences could be explained by the difference in distribution and morphological pattern of amyloid deposition in the renal tissue.